Lethal congenital contracture syndrome: further delineation and genetic aspects. Issue 7 (July 1994) - Vuopala, K; Herva, R
Abstract : In a national morphology based study of lethal arthrogryposis between 1979 and 1992, 40 fetuses and infants with lethal congenital contracture syndrome (LCCS, McKusick 253310) were found in Finland. The incidence of LCCS in Finland was 1:19, 000 births. There were 20 affected males and 20 affected females in 26 families. In 16 cases the pregnancy was terminated after the prenatal diagnosis of total akinesia and fetal hydrops on ultrasound. There were 19 stillborn infants and five were born showing signs of life, but died within one hour. The segregation analyses yielded 0.45 affected by the "singles" method and 0.34 by the "sib" method. The birthplaces of the grandparents were located in the sparsely populated north east of Finland. This finding supports the existence of an autosomal recessive LCCS gene in Finland, particularly in the north eastern part.